Diagnostic Value of Transvaginal Ultrasonography to Determined Degree of Myometrium Invasion in Endometrial Cancer: Nilai Diagnostik Ultrasonografi Transvaginal dalam Menilai Kedalaman Invasi ke Miometrium pada Kanker Endometrium - Kartiwa H. Nuryanto; Selly Fransiska (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objectives: To show transvaginal ultrasound accuracy in determining the degree of myometrial invasion of endometrial cancer within five years in RSCM. Also, to know histopathology characteristics of endometrial cancer according to cell type, degree of invasion, and degree of differentiation of endometrial cancer, within the last five years in RSCM. Methods: This study is a cross-sectional study with a sample of 82 subjects in January 2011 – December 2016 at RSCM. The data were collected by total sampling from cancer registry oncology and gynaecology division of Obstetrics and Gynecology FKUI-RSCM. Results: Transvaginal USG diagnostic test in detection invasion has sensitivity, specificity, PPV, and NPV as 78.79%, 50%, 86.67%, 36.36% respectively. For determine degree of myometrial invasion it has sensitivity, specificity, PPV, and NPV as 81.40%, 76.92%, 79.55%, and 78.90% respectively. Conclusions: Transvaginal ultrasound has better accuracy in determining the degree of invasion compared to detecting myometrial invasion in endometrial cancer. In determining the degree of invasion, its sensitivity and specificity are 81.4% and 76.92%. For detecting any invasion its sensitivity and specificity was only 79.41% and 57.14%. Our study showed that transvaginal ultrasound was an efficient diagnostic tool fo determine further treatment and prognosis in endometrial cancer Keywords: accuracy test, HPV DNA, liquid-based cytology, pre-cervical cancer lesion. Abstrak Tujuan : Mengetahui akurasi USG transvaginal dalam menilai invasi miometrium pada kanker endometrium dalam 5 tahun terakhir di RSCM. Serta karakteristik histopatologi berdasarkan tipe, invasi, dan derajat diferensiasi kanker endometrium dalam 5 tahun terakhir di RSCM Metode :Penelitian potong lintang dengan jumlah sampel 82 subjek pada Jan 2011 – Des 2016 di RSCM. Data dikumpulkan secara total sampling dari registrasi kanker divisi Onkologi Ginekologi FKUI RSCM dan dilakukan uji diagnostik Hasil: Uji diagnostik USG transvaginal menilai ada tidaknya invasi memiliki sensitivitas, spesifisitas, NPP, NPN sebesar 78,79%, 50%, 86,67%, 36,36%. Sedangkan hasil uji diagnostik usg transvaginal dalam menilai derajat invasi memiliki sensitivitas, spesifisitas, NPP, NPN sebesar 81.40%, 76.92%, 79.55%, dan 78.90% Kesimpulan :USG transvaginal dalam menilai derajat invasi lebih baik dibanding menentukan ada tidaknya invasi. Sensitivitas, spesifisitasnya 81,4-% dan 76,92% dibanding 79,41% dan 57,14%. Dalam hal ini USG transvaginal dapat digunakan sebagai alat bantu diagnostik efisien dalam menentukan tata laksana dan prognosis kanker endometrium Kata kunci : kanker endometrium, kedalaman invasi, uji diagnostik, USG transvaginal.